Template-free synthesis of VO2 hollow microspheres with various interiors and their conversion into V2O5 for lithium-ion batteries - Pan, Anqiang (2013)
Getting a charge out of microspheres: Uniform VO2 microspheres with various complex interiors, such as yolk-shelled and multi-shelled hollow structures, have been synthesized through a template-free solvothermal method. After annealing in air, the derived V2O5 microspheres manifest improved electrochemical performance as a high-capacity cathode material for lithium-ion batteries.